2017
DOI: 10.3991/ijet.v12i10.6875
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Testing: Score Equivalence and Testing Administration Mode Preference in a Comparative Evaluation Study

Abstract: The empirical evidences show that two identical Computer-Based Testing (henceforth CBT) and Paper-and-Pencil-Based Testing (henceforth PBT) do not always result in the same scores. Such conclusions are referred to as “the effect of testing administration mode” or “testing mode effect”. Moderators such as individual differences (e.g., prior computer experience or computer attitude) have been investigated [4] to see if they influence test takers’ performance. The Guidelines for Computer-Based Tests and Interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
2
10
0
1
Order By: Relevance
“…The CFLT2 was administered to examine the effect of item review on their performance. Although some researchers have concluded that CFLT version of test resulted in lower scores than in paper-based tests (Chen et al, 2011;Clinton, 2019;Delgao et al, 2018;Golan et al, 2018;Lenhard et al, 2017;Rasmusson, 2015), in this research, the results of the participants' testing performance in both PPBT and CFLT1 revealed that there was not any significant difference between the two sets of scores obtained from the two versions of the reading comprehension test that are in line with some studies (Farinosi et al, 2016;Hashemi Toroujeni et al, In Press;Hermena et al, 2017;Khoshsima et al, 2017h;Kong et al, 2018;Meyer et al, 2016;Prisacari & Danielson, 2017). In fact, participants' performances in two conventional paper-based and computerized testing sessions were not different.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The CFLT2 was administered to examine the effect of item review on their performance. Although some researchers have concluded that CFLT version of test resulted in lower scores than in paper-based tests (Chen et al, 2011;Clinton, 2019;Delgao et al, 2018;Golan et al, 2018;Lenhard et al, 2017;Rasmusson, 2015), in this research, the results of the participants' testing performance in both PPBT and CFLT1 revealed that there was not any significant difference between the two sets of scores obtained from the two versions of the reading comprehension test that are in line with some studies (Farinosi et al, 2016;Hashemi Toroujeni et al, In Press;Hermena et al, 2017;Khoshsima et al, 2017h;Kong et al, 2018;Meyer et al, 2016;Prisacari & Danielson, 2017). In fact, participants' performances in two conventional paper-based and computerized testing sessions were not different.…”
Section: Discussionsupporting
confidence: 89%
“…Use of computer as an integral (Stole et al, 2020) and ubiquitous part of every society (Mullis, Martin, Foy, and Hooper, 2017) raised testing productivity by introducing efficacious tools that have some advantages (Shraim, 2019) such as evaluating responses and giving proper prompt feedback in an intelligent environment (Kilickaya, 2013). Popularity of using computer to improve testing approaches and solve largescale assessment problems that is increasingly growing in recent years (Sawada, 2019) caused entirely practical reconstructions in assessment procedures (Khoshsima and Hashemi Toroujeni, 2017h). In particular, Covid-19 identification late 2019 and health crisis caused by Coronavirus outbreak (WHO, 2020) all over the world (Karim & Hasan, 2020) leaded education systems of especially Asian developing countries to face their greatest challenge because their technology infrastructure was not sufficient (Retnawati, 2015) for digitalized education, and investments on technology (ADB, 2018;Sawada, 2019) is still developing in these countries for a widespread use of computer-based teaching, learning and testing as the new approaches (Karim & Hasan, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of computer technology to improve the quality of test results has been widely carried out. In the era of advanced technology and information, it is very feasible to conduct computer-based tests [4]. Reference [5][6][7] show that testing using a computer is not only able to produce tests that are fast and accurate but can also increase the effectiveness and efficiency of test implementation and maintenance.…”
Section: Introductionmentioning
confidence: 99%